On p-duo Semimodules (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The concept of p-duo semimodule is introduced as a generalization of duo semimodule, where a semimodule M is said to be a p-duo if every pure subsemimodule of M is fully invariant. Many results about this concept are given.